"Partly with and Partly against Her Will": Female Consent, Elopement, and Abduction in Late Medieval Brabant. (October 2017) - Delameillieure, Chanelle
This article addresses the issue of consent in abduction and elopement cases, aiming to contribute to a better understanding of marriage formation in the fifteenth-century duchy of Brabant. It challenges the division between abduction and elopement in current historiography. Whereas some historians believe in the high frequency of elopements as means for youngsters to freely choose their own spouse, I argue that socioeconomic interests motivated most abductions. Although some women certainly succeeded in influencing marital choices themselves, the abduction/elopement was not a frequently used method to oppose social norms and arranged marriages.